Reaksi Pasar Atas Kesepakatan Investasi Bidang Infrastruktur dalam Pertemuan International Monetary Fund-World Bank 2018 - Wahyudhi, P. Sigit; Agung Suaryana, I G. N (E-Jurnal Akuntansi; Vol 27 No 1 (2019)DO - 10.24843/EJA.2019.v27.i01.p23, 2019)
This study aims to examine the capital market reaction to the announcement of infrastructure investment agreements at the International Monetary Fund (IMF) - World Bank annual meeting 2018. Measurement of market reactions in this study uses Cumulative Abnormal Return (CAR). The sample used in this study are companies which engaged in LQ-45 Index on the Indonesia Stock Exchange (IDX) with 7 days observation period. The sampling method used is purposive sampling technique. The data analysis technique used is one sample t-test. Based on the results of the analysis it was found that there is a negative reaction to the announcement of an investment agreement on infrastructure in the 2018 IMF-World Bank annual meeting 2018. This research could be used as a consideration for investors to invest according to company’s external events. Keywords: Market Reaction, Event Study, Abnormal Return, Company External Events